أثر تبني التوظيف الأخضر في أداء المؤسسة: دراسة حالة مؤسسة الأسمنت تبسة - عيشوش, محمد الحافظ (جامعة الوادي - University of Eloued, 2023)
The purpose of this research is to find out the effect of adopting green employment on the performance of the enterprise, and the Taissa Cement Corporation was taken as a sample for the study. It was distributed to a sample consisting of (52) employees at the Tebessa Cement Corporation, and after conducting statistical analyzes using the SPSS program, the study concluded a number of results, the most important of which is that there is a statistically significant effect between the adoption of green employment and performance (efficiency, effectiveness, productivity) in the cement corporation. Tebessa, this research also presented a set of recommendations.
The impact of adopting green employment on the performance of the institution :Case study of the Cement Corporation of Tebessa
مقال
Keywords: التوظيف الأخضر ; الأداء; green recruitment; performance.